PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KREATIVITAS BELAJAR SISWA DI RAUDHATUL ATHFAL PLUS FATAHUL WARDAH PALEMBANG - Afifah, Annisatul; Hartatiana; Bahtiar, Adi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the limitations of less varied learning, making students tend to be passive in learning activities. In addition, inadequate learning media also limits children's creativity. This study aims to determine the effect of the project-based learning model on student learning creativity at RA Plus Fatahul Wardah Palembang. This study used one experimental class. With a quantitative research approach. The design of this study was one group pre-test post-test design. The sample of this study amounted to 9 children in class B2 at RA Plus Fatahul Wardah Palembang. Data collection techniques were by observation, testing, and documentation. Data analysis techniques used validity tests, reliability tests, normality tests, homogeneity tests, and t-test hypothesis tests. Based on the results of the study, there is a difference in the results of the pre-test and post-test with an average pre-test value of 35, while the average post-test value is 74. Furthermore, based on the results of the t-table calculation for a significance level of 0.05%, the calculated t-value> t-table (-24.535> 2.306) can be concluded that H0 is rejected and Ha is accepted, so it can be said that there is an influence of the use of the project-based learning model on student learning creativity at RA Plus Fatahul Wardah Palembang.